齿轮综合修形方法的研究 - 徐香翠; 宋爱平; 张礼峰; 黄建伟 (Jixie chuandong)
In the course of gear pair transmission,the elastic deformation and installation error are the main source of causing transmission error.A new method—comprehensive modification for improving gear pair transmission steadiness and bearing capacity is puts forward through analyzing the shortage of profile modification and axial modification.The related parameters of the comprehensive modification are determined according to the elastic deformation law of gear mesh and the calculation formulas are deduced.Finally,the comprehensive modification can obviously improve the tooth surface stress state is verified by finite element analysis method.